Lipase Production by Some Aquatic Phycomycetes in Maiduguri a Semi-Arid Area of Nigeria - C.E, Odu,; C.I.C, Ogbonna,; O.O.C, Chukwu,.; I.A., Onyimba,; J.B.,, Ndirmbula, (European Scientific Journal, ESJ, 2017)
Studies on the abilities of three species of aquatic phycomycetes isolated from the semi arid zone of Nigeria in Maiduguri, Borno State to produce lipase was carried out. The isolates included Allomyces anomalus, Allomyces arbuscular and Brevilegnia diclina. These three test aquatic phycomycetes were isolated using baiting technique with hemp seeds and pure cultures maintained on malt extract agar for lipase production. Plate assay and culture broth assay methods using mineral salts medium with tween 80 in conjunction with Olive oil and Mustard seed oil as lipase inducers were used in assessing the abilities of the isolates in producing lipase. The three isolates of aquatic phycomycetes showed via the plate assay method abilities to produce lipase with evidence of halo formation around colonies without stains and separately with intensification of halo formation with methyl red and sudan III indicators. Allomyces anomalus recorded the highest growth and halo diameter followed by Allomyces arbuscular and least by Brevilegnia diclina. Lipase level was not detectable using the culture broth method. Lipase production by aquatic phycomycetes have not been encountered from available literature, hence this preliminary result needs to be optimised fully to exploit new opportunities of lipase production from these group of aquatic fungi.